Development of a software application for teaching computer networking - Wang, Jason Shicheng (Nanyang Technological University, 2021)
In a typical classroom, an individual student takes instructions from a teacher, memorises a concept to the best of their ability, and then regurgitates the theory in an exam with or without a full understanding of the problem. However, research has shown that this is not an effective way of learning, with most of the newly learnt information lost within a week. As such, gamification is proposed to solve this issue by creating a software that teaches networking concepts in an engaging manner for students to learn at their own pace. Gamification refers the use of game design elements and principles outside of games, for example in an e-learning software. This has been shown to make learning more enjoyable and effective, while also promoting independent learning. The hands-on nature also increases immersion for many students, allowing them to put the theoretical principles into use with practical examples. This is especially important in the current context of home-based learning due to the ongoing pandemic, causing a decrease in physical contact, communication between students and lab sessions. There is also currently a shortage of well-qualified engineers in this area, and this has serious implications due to how widely computer networking is used in our daily lives. This project aims to create an application to teach networking, more specifically the shortest path between nodes in a graph using the Dijkstra’s Algorithm. The app is made of up of three distinct parts, the exercise, the web app and the game. It is hoped that this will appeal to more students to study networking by making it more fun and engaging. This report focuses on the early concepts and ideas for the project, as well as the working versions of the game created using both Unity and JavaScript. More work will need to be done to make this a full-fledged application suitable for deployment to the general student population, and this report will also go in-depth on the difficulties faced as well as all the workarounds and solutions to these issues.